Affinities and Taphonomy of a Cambrian Discoid from Guizhou, South China. (March 2014) - Yang, Xinglian; Zhao, Yuanlong; Wu, Weiyi; Sun, Zongyuan; Zheng, Haolin; Zhu, Yajie
Abstract : Disc-like fossils from siltstones of the Taozichong Formation (Cambrian) in the Qingzhen area, Guizhou, South China are reported here. They are similar to some Ediacaran and Phanerozoic discoidal fossils, and assigned to Tirasiana ? disciformis ? Palij, 1976. Based on the study of 43 specimens, dewatering or fluid escape structures, soft-sediment loading, scratch circles or other inorganic origins are ruled out, and the fossil is interpreted as a discoidal body fossil of unknown affinities rather than trace fossils. Energy-dispersive X-ray spectroscopy and elemental mapping analyses reveal that the discoid fossils contain higher concentrations of C, Fe, and P than the surrounding matrix, indicating the possible presence of pyrite, apatite, and organic carbon as a result of authigenic mineralization in association with decay and early diagenetic processes. The possible presence of extracellular polymeric substance suggests that the discs were surrounded by thin microbial mats composed primarily of extracellular polymeric substances, which facilitated their fossilization by promoting conditions that are favorable to secondary mineral precipitation. The new specimens provide useful information about the phylogenetic affinities of these early discoidal fossils and help us to better understand the taphonomic modes of non-biomineralizing organisms in Ediacara-type and Burgess Shale-type biotas.